Natural Compounds Activities against SARS-CoV-2 Mpro through Bioinformatics Approaches for Development of Antivirus Candidates - Taufik Muhammad Fakih (Jurnal Kimia Sains dan Aplikasi, 2021)
Coronavirus infection (COVID-19) caused by SARS-CoV-2 appears as a pandemic that has spread to almost all countries in the world. Antiviral therapy using natural compounds is one alternative approach to overcome this infectious disease. The therapeutic mechanism is proven effective against the main protease (Mpro) of SARS-CoV-2. This research aims to perform bioinformatics studies, including ligand-docking simulations and protein-protein docking simulations, to identify, evaluate, and explore five compounds' activity on SARS-CoV-2 Mpro and their effects against Angiotensin-Converting Enzyme 2 (ACE-2). Protein-ligand docking simulations show kaempferol, flavonol, and their glycosides (Afzelin and Juglanin) and other flavonoids (Quercetin, Naringenin, and Genistein) have a high affinity towards SARS-CoV-2 Mpro. These results were then confirmed using protein-protein docking simulations to observe the ability of five compounds to prevent the attachment of ACE-2 to the active site. Based on the results of the bioinformatics studies, Quercetin has the best affinity, with a binding free energy value of −33.18 kJ/mol. The five compounds are predicted to be able to interact strongly with SARS-CoV-2. The results in this research are useful for further studies in the development of novel anti-infective drugs for COVID-19 that target SARS-CoV-2 Mpro.